PTU-077 A pilot international survey of colonoscopy related injury in colonoscopists. (8th June 2018) - Al-Rifaie, Ammar; Hodge, Stephen; Thoufeeq, Mo; Donnelly, Mark
Abstract : Introduction: Colonoscopy is physically demanding for endoscopists and for patients. Repetitive movements during colonoscopy can lead to overuse injuries. Our aim is to explore the prevalence and range of colonoscopy-related musculoskeletal injuries (CRI) in endoscopists. Methods: A cross-sectional electronic survey of 1825 endoscopists was made. The sample was comprised of members of British Society of Gastroenterology, European Society of Gastrointestinal Endoscopy and National Nurse Endoscopy Group. The survey comprised 20 questions. These included: endoscopists' workload, level of experience and their perceived CRIs. All endoscopists who perform colonoscopy independently were included in the analysis. Results: Initial results include 337 completed questionnaires out of 1825 (18.4%). Of those, 319 (94.5%) participants are fully independent in colonoscopy. 254 out of 319 (79.6%) have experienced musculoskeletal injuries. These were reported as either possibly (n=143, 46.7%) or definitely (n=90, 29.4%) related to colonoscopy. Factors that were significantly associated with higher rates of CRI:>6 hours per week (equivalent to 2 or more lists/week) (p=0.0001), >5000 life-time number of colonoscopies performed (p=0.0002), >150 procedure performed per year (p=0.0001). Female endoscopists are also at a significantly higher risk of CRI and more likely to require time off-work (p=0.0001). Commonly injured areas were: lower back (n=95, 30.45%), neck (n=90, 28.85%) and left thumb (n=80, 25.64%). 95 (30.35%) of injured endoscopists applied some modification to their practice e.g. stretching exercises and ergonomic changes. 130 (48.5%) endoscopists thought that repetitive hand movements was a likely causative mechanism. 125 (46.6%) believed that torqueing the scope and body position were precipitating CRI. Several treatment modalities were used; physiotherapy (n=109), medications (n=70), rest (n=43), splinting (n=31), steroid injections (n=26) and surgery (n=11). Conclusions: From our initial results, a significant proportion of endoscopists experience CRI. Higher prevalence of CRI was significantly associated with >5000 total life-time colonoscopies, >6 hour/week performing colonoscopy, >150 procedure/year and female gender. These results highlight the need to recognise CRI as an important issue and to adopt preventative strategies routinely in the future.